A descriptive study of nail changes in systemic diseases - Chanabasappa Mendagudli; Sanjay Ramachandra Thejaswi; M Ramesh; Mohan Eshwar Rao Shendre; Anila Sara Thampi; R Ankitha (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: Nail findings may represent a part of the symptom complex that may be useful for the physical diagnosis. Thus, the present study was undertaken to know the nail changes in systemic diseases among patients attending the outpatient and inpatient departments of dermatology, medicine, nephrology, pulmonology, and surgery attached to Karnataka Institute of Medical Sciences (KIMS), Hubballi. Methodology: A hospital-based original study was conducted at KIMS, Hubballi. During January 1, 2021-January 30, 2023, data were collected by personal interview after obtaining informed consent from all eligible participants using a prestructured and pretested pro forma, among a convenient sample of 272 patients selected by the simple random sampling method. Results: Among 272 patients, 57.5% of the patients were young adults with male predominance (56.0%) and inpatients (66.0%) were more compared to outpatients (44%). Of the 272 patients, respiratory system (RS) (26%) was most common involved followed by hematology (21.0%), gastrointestinal tract (GIT) and liver (17%), cardiovascular system (CVS) and renal (12%), and clubbing was the most common nail change encountered (35.5%) followed by longitudinal ridging (33%) and pallor (31%) of the nail subsequently. RS was found as the common cause of clubbing followed by CVS and liver and GIT. Conclusion: RS (clubbing) was the most common system involved. Other systems involvement were renal system (half and half nail), liver, and GIT system (Terry's nail) which are the specific nail changes that can lead us to the diagnosis. Thus, nails can serve as a window for the underlying systemic illness.